Preparation and characterization of semi-silica insulation refractory by utilizing lignite fly ash waste materials - Debnath N.K.; Pabbisetty V.K.; Sarkar K.; Singh A.; Majhi M.R.; Singh V.K. (My University, 2025)
A tremendous amount of lignite fly ash (FA) is produced as waste materials in coal-fired thermal power plants. These wastes materials contain toxic elements which are detrimental to the environment. In this study, the lignite FA waste materials are used as the primary raw material for the fabrication of semi-silica insulation refractory bricks to reduce the environmental pollutions. Lignite FA from coal-fired thermal power plant NLC India Ltd., Bikaner in northern India, ball clay, and sawdust are the main components of semi-silica insulation refractory bricks. FA and ball clay were blended in various combinations, and sawdust is used as a pore former in the refractory bricks. The prepared samples were fired in the range of 1000 °C to 1200 °C for 2 h. The resultant properties of these bricks were characterized in terms of mechanical, thermal, phase analysis, and microstructure. It was found that FA can be used as a suitable candidate in the preparation of semi-silica insulation refractory bricks. The chemical analysis, bulk density (BD), apparent porosity (AP), and thermal conductivity (TC) of the insulation refractory bricks prepared with lignite FA were observed to be similar to the commercial products. The sample FC30S, which contains 60% lignite FA, 30% ball clay, and 10% sawdust showed 44.69% AP and 0.38 W/mK thermal conductivity after sintering at 1100 °C for 2 h. Hence, the use of FA is technically feasible, economically beneficial, and can be used as thermal insulation refractory. The study indicates a sustainable technique of using fly ash for the fabrication of eco-friendly semi-silica insulation refractory. © 2022 Elsevier Ltd